Impact of generational differences on the perception of employee attributes in relation to employee performance: A conceptual model - Anthonysamy , Lilian; Kunaratnam, Praveena; Alias , Mazni (International Journal of Accounting, Finance and Business, 2025)
Employee performance has become more challenging for managers to manage with a diversified workforce in terms of age, background, lifestyle, upbringing, and exposure to technological advancement, that has flooded the industry. The variation in the age of this workforce poses the management with a new task to effectively manage them. Each generation having its own personality and characteristics, has a different perspective on problems and knowledge. Employee performance is vital to organizational productivity and therefore workplace motivation is crucial. Due to their generational differences, they have different viewpoints or stance on certain employee traits that affect the employee performance. Employee attributes impact both the aims and strategy of the company as well as the performance of its employees so it’s important for an organization to consider these traits and attributes. Goal of this research is to understand the influence of generations on employee attributes and their eventual impact on employee performance. The focus of this study will be on generation X, Y and Z. This research offers both theoretical and practical insights. It shows the connection on how important the perceptual variations to performance results, theoretically advancing on generational impacts in organizational behaviour. Effectively, it gives organizational leaders evidence-based methods to improve generational alignment in work practices, which in turn improves employee motivation and organizational